EM-IOT: IoT-Based Battery Monitoring System and Location Tracking on Electric Vehicles - Tasya Thifali Salsabila; Haikal Faiz Ramadhan; Iftitah Imawati; Dwi Ana Ratna Wati (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
As the community increasingly embraces electric vehicles over time, there is a growing necessity for electric vehicle users to determine the real-time status of their batteries and their locations. This enables them to estimate when and where their electric vehicle batteries will need to be recharged. The battery condition can be used to estimate the remaining distance that the electric vehicle can travel while monitoring and observing the location of the electric vehicle is required for security and can also be used as a suggestion for electric vehicle users to carry out charging by adding information on the location of the nearest charging station. The EM-IOT system is designed to be accessible via an Android smartphone with an easy-to-understand and attractive user interface. The wireless system is designed with the ES12E module and the Thingspeak platform. Testing is done to ensure the system can work properly. The test results of battery monitoring and location tracking on the EM-IOT application have been able to display data with an average error not exceeding 5%. The data on the application is updated every 15 seconds. The EM-IOT system can function properly to monitor battery voltage, battery percentage, remaining distance, and the current location of the system vehicle.